2020
DOI: 10.1177/2324709620984603
|View full text |Cite
|
Sign up to set email alerts
|

Rhabdomyolysis in Patients Hospitalized With COVID-19 Infection: Five Case Series

Abstract: The novel SARS-CoV-2 virus (severe acute respiratory syndrome coronavirus 2) is now known to cause acute respiratory distress, cytokine storm, and coagulopathy. Multiple other manifestations have been published in recent literature. Rhabdomyolysis is a syndrome of muscle damage, with release of intracellular contents into circulation. It is characterized by marked elevations of creatinine kinase levels and myoglobinuria. In this article, we describe a series of 5 cases who were admitted with COVID-19 pneumonia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
28
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 11 publications
0
28
0
3
Order By: Relevance
“…The mechanism behind SARS-CoV2 causing rhabdomyolysis is not clear. However, viral cell invasion and cytokine-mediated direct muscle cell damage have been implicated [ 19 ]. Notably, Type II pneumocyte cytoplasm in early stages and colonic mucosa in COVID-19 patients presented with diarrhea contained the viral particles [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism behind SARS-CoV2 causing rhabdomyolysis is not clear. However, viral cell invasion and cytokine-mediated direct muscle cell damage have been implicated [ 19 ]. Notably, Type II pneumocyte cytoplasm in early stages and colonic mucosa in COVID-19 patients presented with diarrhea contained the viral particles [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…1 Four patients developed renal insufficiency during hospitalization and 2 patients died. 1 It was concluded that the pathophysiology of SARS-CoV-2-associated rhabdomyolysis requires clarification. 1 The study is appealing but raises comments and concerns.…”
mentioning
confidence: 99%
“…Additionally, other potential causes for renal insufficiency (eg, diabetes) were present in patients 2 to 5. 1 A second shortcoming is that the medication the 5 patients were receiving during hospitalization was not considered as a trigger of hyper-CKemia. Patient 1 received azithromycin and tocilizumab.…”
mentioning
confidence: 99%
See 2 more Smart Citations